Trade unions of the world - Gale Group (London, England John Harper Publishing, 2005)
This comprehensive resource covers trade unions in every independent country in the world. Entries feature detailed coverage of key unions; details of trade union centers, including contact information, Web site URLs, international affiliations and more; discussion of the political and economic backgrounds against which the unions operate; an overview of trade unionism; and more.
About the contributors -- About ICTUR -- Preface -- Afghanistan - Zimbabwe -- Appendix: International and regional organizations -- Index.
Electronic reproduction.
Keywords: Labor unions; Industrial relations; Labor unions -- Directories; Electronic books